Analysis of The Implementation of Transparency and Accountability in Zakat, Infaq, and Alms Institutions (Case Study of Baitul Maal Xyz Foundation) - Hafidz Ridho Ansori; Evony Silvino Violita (Green Publisher Indonesia, 2025)
This research focuses on the implementation of transparency and accountability principles in the management of zakat, infak, and sedekah (ZIS) funds by Yayasan Baitul Maal XYZ (YBM XYZ). The primary challenge faced by zakat management institutions is ensuring the trustworthy management of funds in compliance with shariah principles, as expected by the community. The objective of this study is to evaluate the extent to which YBM XYZ has implemented transparency and accountability principles in the management of ZIS funds in 2023. The research employs a case study method with a qualitative approach. Data collection was conducted through semi-structured interviews with YBM XYZ’s internal stakeholders and document analysis, including annual financial reports and program reports. The findings reveal that YBM XYZ has successfully met most of the indicators for transparency and all indicators for accountability. In the transparency aspect, the institution met 15 out of 17 evaluated indicators. Two indicators that were not fulfilled pertain to the quality of financial reporting, specifically the use of an integrated financial information system such as SIMBA (Sistem Informasi dan Manajemen BAZNAS), and the lack of ISO certification as part of the organization’s governance. Despite these limitations, YBM XYZ regularly publishes financial reports through various media and provides accessible information for stakeholders. On the accountability aspect, YBM XYZ successfully met all defined indicators. The operational efficiency of using only 10% of the collected funds for operational costs (lower than the national standard of 12.5%) reflects the organization’s commitment to economical and responsible management.